Batch Kinetics of Nutrients Removal from Synthetic Meat Processing Wastewater by using Microalgae Botryococcus Sp. - A. Shanmugan, Vikneswara; M.S.R. Mohammed, Radin; H.B.M. Kassim, Amir; A.S. Al-Gheethi, Adel; A.A. Latiffi, Nur (International Journal of Engineering and Technology, 2018)
Disposed meat processing wastewater contains high range of nutrients such as ammonia nitrogen and orthophosphate which will cause eutrophication and lead to destruction of ecosystem. Therefore, batch experiments were conducted to explore the influence of the range of initial concentration of ammonia nitrogen and orthophosphate found in meat processing wastewater in the removal of those nutrients during phycoremediation of synthetic wastewater by using microalgae Botryococcus sp. Michaelis-Menten rate expression was applied to generate biokinetic coefficients k, reaction rate constant, Km, half saturation constant and Y, yield coefficients. The experiment was conducted using synthetic wastewater with initial NH4-N concentration varying between 30-480 mg/l and PO43- concentrations varying between 14-239 mg/l. The results demonstrate removal efficiency of NH4-N between 42-100 % and PO43- between 63-96 %. Biokinetic coefficients were established as k = 1.72 mg NH4-N /mg chl a/day, Km = 52.29 mg/L and YN = 0.027 mg chl a/mg NH4-N for ammonia nitrogen and k = 1.13 mg PO43-/mg chl a/day, Km = 44.45 mg/L and YP = 0.038 mg chl a/mg PO43- for orthophosphate.Â Â